LiTi2(PO4)3/C Anode Material with a Spindle‐Like Morphology for Batteries with High Rate Capability and Improved Cycle Life. Issue 7 (2nd June 2016) - Yu, Shicheng; Tempel, Hermann; Schierholz, Roland; Aslanbas, Özgür; Gao, Xin; Mertens, Josef; de Haart, Lambertus G. J.; Kungl, Hans; Eichel, Rüdiger‐A.
Abstract: Nanocrystalline LiTi2 (PO4 )3 /C has been synthesized by employing a solvothermal process in which oxalic acid was used as a solubilizer for the titanium source, a surfactant, and a carbon source. Additionally, Pechini's sol–gel‐based method was also used as the synthesis method for comparison. LiTi2 (PO4 )3 /C prepared by using a solvothermal route showed a homogenous particle size with spindle‐like microstructures formed from self‐assembled nanosized‐platelets, whereas preparation by the sol–gel process resulted in agglomerated powders with irregular morphology and particle size. The different morphologies of LiTi2 (PO4 )3 /C prepared in the two synthesis methods tend to form different electrode layer structures, which results in remarkable differences in their electrochemical properties. In particular, the solvothermally synthesized LiTi2 (PO4 )3 /C composite exhibits superior high‐rate‐discharge capability and cycling stability. A capacity of approximately 97.7 % of the initial capacity was maintained for the solvothermal sample after 500 cycles at 5 C. Abstract : What′s in a shape? Lithium titanium phosphate powders have been prepared by using a solvothermal process and compared with the same product from a Pechini‐based sol–gel route. The superior properties of the solvothermally prepared powder in electrochemical studies result from its different morphology. The development of the morphology during the solvothermal process has been investigated (see figure).